2017
DOI: 10.1007/s11367-017-1357-0
|View full text |Cite
|
Sign up to set email alerts
|

Erratum to: Life cycle assessment of chitosan production in India and Europe

Abstract: The life cycle impact assessment (LCIA) results for the Indian chitosan supply chain, as published in the article, contain an error in the BWater use^indicator. While water use during chitin and chitosan manufacturing were accounted for in the inventory analysis (167 L/kg chitin and 250 L/kg chitosan, see section 3.2 in the article), these flows were not covered in the impact assessment calculations, thus leading to an underestimate of the overall water use in the supply chain. In Table 1 and Table 2 below, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 0 publications
1
8
2
Order By: Relevance
“…The higher scores obtained in this study are primarily because of the more processes impacting the environment than similar literature. 23 , 24 , 39 Even with more processes considered, the current study showed scores below the baseline. The higher values obtained in this study can be attributed to the type and the method for environmental impact assessment.…”
Section: Results and Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…The higher scores obtained in this study are primarily because of the more processes impacting the environment than similar literature. 23 , 24 , 39 Even with more processes considered, the current study showed scores below the baseline. The higher values obtained in this study can be attributed to the type and the method for environmental impact assessment.…”
Section: Results and Discussioncontrasting
confidence: 63%
“… 22 On the other hand, Muñoz et al analyzed and compared the life cycle of chitosan production from shrimp shells and crab shells in two different manufacturing locations in India and Europe. 23 , 24 They have focused on chitosan production’s environmental performance taking the process conditions and reagents into account to obtain chitosan.…”
Section: Introductionmentioning
confidence: 99%
“…The decolorization step in chitosan production design in the current study is based on ethanol, which increases some of the environmental impacts in LCA. Besides that, Muñoz et al 23 did not include the decolorization step in their LCA analysis; this is why the study in Ecuador shows a higher impact of the non-carcinogenic toxicity category.…”
Section: Impact Category Unit Valuementioning
confidence: 99%
“…For this purpose, Gómez-Ríos et al reported a technical design for the chitosan production plant in Colombia with a plant simulation, equipment with dimensions, and costs analysis associated with the plant designed 22 . On the other hand, Muñoz et al analyzed and compared the life cycle of chitosan production from shrimp shells and crab shells in two different manufacturing locations in India and Europe 23 . They have focused on chitosan production's environmental performance taking the process conditions and reagents needed into account to obtain chitosan.…”
Section: Introductionmentioning
confidence: 99%
“…Muñoz et al23 studied the life cycle of chitosan production in India and Europe. Since Muñoz et al have considered using shrimp shells for chitosan production in India, the finding comparisons between that study and this study are very realistic.…”
mentioning
confidence: 99%